CHANGES IN FISHING PATTERN FROM SURFACE TO DEEP LONGLINE FISHING BY THE INDONESIAN VESSELS OPERATING IN THE INDIAN OCEAN - Lilis Sadiyah; Natalie Dowling; Budi Iskandar Prisantoso (Indonesian Fisheries Research Journal, 2011)
(P.T. Perikanan Samodra Besar) data are a valuable source, since they are the longest time series of catch and effort data available from the fishery. This paper aimed to interpret the spatial and temporal catch and effort trends to the extent possible and to reconcile apparent changes in targeting practices against the actual catch. Catch and effort data collected by P.T. Perikanan Samodra Besar from its Benoa-based longliners during 1978-1995 were summed to obtain annual catch, effort, and catch per unit of effort trends. To generate spatial distributions of catch and effort, catch and effort data were aggregated by 5-degree squares. The data showed that P.T. Perikanan Samodra Besar vessels commenced deep longlining in 1983, i.e. 56% of the total sets in 1983 using 10 or more hooks between floats. Prior to that, P.T. Perikanan Samodra Besar vessels used 6 hooks between floats,which resulted in a larger amount of yellowfin tuna (Thunnus albacares) as well as overall tuna catch. However, bigeye tuna (Thunnus obsesus) catch per unit of effort only increased from 1992. The increase in big eye tuna catch per unit of effort coincided with a reduced fishing range and concentration within an area where P.T. Perikanan Samodra Besar had not previously experienced high big eye tuna catches, as opposed to focusing their effort on areas where they had historically caught big eye tuna. In the absence of supplementary information, and assuming that the switch to deep longlining in 1983 was done to target big eye tuna, the analysis suggests that the outcome of P.T. Perikanan Samodra Besar fishing activities between 1983 and 1991 were inconsistent with their objectives.